Collaboration or Collision? Identity Formations and Resource Management : The Case of Kodagu, Karnataka - Arnbjerg,Rasmus Bay (2005)
This study's purpose was to focus on collective identity and its effect on approaches to natural resource management. Within development studies in general, and in studies on resource management in particular, there is a theoretical need for putting more emphasis on contextual variables. One such variable, it was argued, is "identity". Putting emphasis on a triadic relationship between the collective identity, its relation to other collective identities, and the political environment in which these identities function, the study found that the issue of identity - when activated - plays an important role in the way a collective identity may perceive the possibility for collaboration in relation to natural resources and its management.
Keywords: identity; identitet; collective identity; resource management; development studies; South Asia; Social structures; Sociala strukturer; Social geography; Socialgeografi